Relationship between marine epilithic diatoms and environmental variables in oligotrophic bay, NE Mediterranean - HAFNER, DUBRAVKA; CAR, ANA; JASPRICA, NENAD; KAPETANOVIĆ, TATJANA; DUPČIĆ RADIĆ, IRIS (Mediterranean Marine Science, 2018)
The taxonomic composition and structure of a marine epilithic diatom community were sampled from the bottom of the two sites at monthly intervals from January to December 2011 in the small semi-enclosed oligotrophic Neum Bay in Bosnia and Herzegovina (Middle Adriatic). Altogether, 264 diatom taxa (species and infraspecific taxa) within 69 genera were identified. Among them, 149 and 203 taxa occurred in samples from the shallow (0.5 m depth) and deep (8 m depth) sites, respectively. The monthly distribution of most of the diatoms was irregular and high numbers of sporadic taxa were found. SIMPER analysis indicated that the difference between shallow and deep sites could be largely attributed to the frequently recorded diatom taxa and those with high percentage abundances. They were Halamphora coffeiformis, Caloneis excentrica, Cocconeis scutellum var. scutellum, Licmophora flabellata, Licmophora gracilis, Licmophora sp., Navicula abunda, Rhabdonema adriaticum, and Striatella unipunctata. Canonical Correspondence Analysis (CCA) showed that temperature, oxygen saturation (O2/O2′), silicate concentration (SiO4), and salinity were the most important factors influencing diatom community structure in the bay.